Stronger vection in junior high school children than in adults - Shirai, Nobu; Imura, Tomoko; Tamura, Rio; Seno, Takeharu (Frontiers in Psychology, 2014)
Previous studies have shown that even elementary school-aged children (7 and 11 years old) experience visually induced perception of illusory self-motion (vection) (Lepecq et al., 1995, Perception, 24, 435–449) and that children of a similar age (mean age = 9.2 years) experience more rapid and stronger vection than do adults (Shirai et al. 2012, Perception, 41, 1399–1402). These findings imply that although elementary school-aged children experience vection, this ability is subject to further development. To examine the subsequent development of vection, we compared junior high school students’ (N = 11, mean age = 14.4 years) and adults’ (N = 10, mean age = 22.2 years) experiences of vection. Junior high school students reported significantly stronger vection than did adults, suggesting that the perceptual experience of junior high school students differs from that of adults with regard to vection and that this ability undergoes gradual changes over a relatively long period of development.